2022
DOI: 10.4103/shb.shb_90_21
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Emergency Public Activity Restrictions on COVID-19 Epidemiological Parameter in East Java Province, Indonesia

Abstract: Introduction: This study was aimed to analyze the effectiveness of the emergency activity restriction policy implementation to slow down the daily incidence and mortality of COVID-19 in the East Java Province of Indonesia. Methods: An ecological study design was used for this research as the data were acquired from the daily confirmed cases and mortality reports of COVID-19 in 29 regencies and 9 cities in East Java Province of Indonesia from June 14 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Due to its seriousness and pervasiveness, the World Health Organisation (WHO) declared it a pandemic in 2020 [1]. The devastating effect of this pandemic on economic activities [2][3][4], health [5][6][7][8][9][10][11], and sociocultural lifestyle [12][13][14][15][16][17] around the world is very distressing. The number of COVID-19 cases keeps increasing, with the current global infection being over 513 million cases and fatalities over 6.2 million as of 5 May 2022 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its seriousness and pervasiveness, the World Health Organisation (WHO) declared it a pandemic in 2020 [1]. The devastating effect of this pandemic on economic activities [2][3][4], health [5][6][7][8][9][10][11], and sociocultural lifestyle [12][13][14][15][16][17] around the world is very distressing. The number of COVID-19 cases keeps increasing, with the current global infection being over 513 million cases and fatalities over 6.2 million as of 5 May 2022 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors including the perceived vaccine’s efficacy or safety, lobbying by anti-vaccination groups, and the accelerated vaccine research and production, were all found to be significant [ 26 ]. Evidence suggests that preventative behaviors or policies might be useful in pandemic control [ 27 , 28 ]; nevertheless, it may not be always effective [ 29 , 30 ]. These imply that it’s important to promote the COVID-19 vaccine and focus on herd immunity to prevent the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions: Stimulation of toddler growth and development can be carried out by all family members, who during the pandemic period, all activities are carried out from home. It is recommended that mothers actively coordinate with village midwives online and offline during the COVID- 19 As a result of the pandemic, all activities involving the community that have the potential to assemble have been postponed due to the determination of the COVID-19 pandemic as a non-natural disaster (2-5) and efforts to inhibit the spread of the virus with the issuance of rules regarding large-scale restrictions issued by the Jombang Regent (6)(7)(8)(9). During the COVID-19 pandemic, a mother's independence is needed to stimulate toddlers' optimal growth and development.…”
Section: Resultsmentioning
confidence: 99%